2005
DOI: 10.1002/hep.20631
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal concentrations of esterified carnitine in bile

Abstract: The etiology of acute liver failure in children is unknown in a large number of cases. Defects in fatty acid oxidation have been shown to lead to severe liver injury. This retrospective analysis examined the bile acylcarnitine profiles of 27 children with acute liver failure who underwent liver transplantation or died. Results were compared with 758 postmortem samples from individuals without acute liver failure. Cumulative amounts of free carnitine, medium-or long-chain species in excess of the 95th percentil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…FAO dysfunction can lead to both hepatocytic and cardiomyocytic injury in children with inherited FAO disorders. 43 Hypoglycemia and elevated CPK levels, seen in severe FAO disorders, were not more common in our HEU newborns with abnormal ACP, again suggesting that in the first week of life FAO dysfunction is subclinical and mild. Furthermore, lactate, which is a clinical biomarker of OXPHOS dysfunction, was not significantly increased in those newborns with abnormal ACP.…”
Section: Discussionmentioning
confidence: 48%
“…FAO dysfunction can lead to both hepatocytic and cardiomyocytic injury in children with inherited FAO disorders. 43 Hypoglycemia and elevated CPK levels, seen in severe FAO disorders, were not more common in our HEU newborns with abnormal ACP, again suggesting that in the first week of life FAO dysfunction is subclinical and mild. Furthermore, lactate, which is a clinical biomarker of OXPHOS dysfunction, was not significantly increased in those newborns with abnormal ACP.…”
Section: Discussionmentioning
confidence: 48%
“…Finally, acute liver failure in a young infant may be a dramatic presentation of an inborn error of metabolism unmasked by a metabolically stressful event such as surgery. In our patient, detection of aberrant organic acids and carnitine species suggested a disorder of fatty acid oxidation (Shneider et al, 2005). However, detection of these substances at the time of acute hepatic necrosis associated with extreme oxidant stress would not be surprising.…”
Section: Discussionmentioning
confidence: 86%
“…Previous work from the PALF group suggested that there were underlying abnormalities in FAO even in patients with another diagnosis 7. Because many of the metabolic diseases affect the newborn, some centers may rely on the newborn screening for young infants.…”
Section: Discussionmentioning
confidence: 99%